A framework for improving early detection of breast cancer in sub-Saharan Africa: A qualitative study of help-seeking behaviors among Malawian women. Issue 1 (January 2017) - Kohler, Racquel E.; Gopal, Satish; Miller, Anna R.; Lee, Clara N.; Reeve, Bryce B.; Weiner, Bryan J.; Wheeler, Stephanie B.
Highlights: This is the first study to describe the breast cancer help-seeking pathway in Africa. Malawian patients were largely unaware of breast cancer, which led to long delays. Complex individual, interpersonal, health system, and social factors affected access. The proposed framework identifies areas for interventions to improve early detection. A multi-level approach to improve breast cancer early detection is needed. Abstract: Objective: Many women in Africa are diagnosed with advanced breast cancer. We explored Malawian breast cancer patients' perspectives about their diagnosis and ability to access care to identify help-seeking behaviors and to describe factors influencing delay. Methods: We purposively sampled 20 Malawian breast cancer patients to conduct in-depth interviews. Transcripts were double coded to identify major themes of breast cancer help-seeking behaviors and what delayed or facilitated access to care. Results: We outlined a breast cancer help-seeking pathway describing decisions, behaviors, and interactions from symptom presentation to receipt of cancer care. Patients were largely unaware of breast cancer and did not immediately notice or interpret symptoms. As symptoms progressed, women inferred illness and sought help from social networks, traditional remedies, and medical care. Economic hardship, distance to the facility, provider knowledge, health system factors, and social norms often delayed reaching the facility, referrals, diagnosis, and receipt of care. Conclusions: Social-contextual factors at the individual, interpersonal, health system, and societal levels delay decisions, behaviors, and access to breast cancer detection and appropriate care. Practice implications: A comprehensive approach to improving breast cancer early detection must address public awareness and misconceptions, provider knowledge and communication, and cancer care delivery.